NAC transcription factors in plant multiple abiotic stress responses: progress and prospects - Shao, Hongbo; Wang, Hongyan; Tang, Xiaoli (Frontiers in Plant Science, 2015)
Abiotic stresses adversely affect plant growth and agricultural productivity. According to the current climate prediction models, crop plants will face a greater number of environmental stresses, which are likely to occur simultaneously in the future. So it is very urgent to breed broad-spectrum tolerant crops in order to meet an increasing demand for food productivity due to global population increase. As one of the largest families of transcription factors in plants, NAC transcription factors play vital roles in regulating plant growth and development processes including abiotic stress responses. Lots of studies indicated that many stress-responsive NAC transcription factors had been used to improve stress tolerance in crop plants by genetic engineering. In this review, the recent progress in NAC transcription factors was summarized, and the potential utilization of NAC transcription factors in breeding abiotic stress tolerant transgenic crops was also be discussed. In view of the complexity of field conditions and the specificity in multiple stress responses, we suggest that the NAC TFs commonly induced by multiple stresses should be promising candidates to produce plants with enhanced multiple stress tolerance. Furthermore, the field evaluation of transgenic crops harboring NAC genes, as well as the suitable promoters for minimizing the negative effects caused by over-expressing some NAC genes, should be considered.